2017
DOI: 10.1111/apm.12770
|View full text |Cite
|
Sign up to set email alerts
|

Dominant high expression of wild‐type HSP110 defines a poor prognostic subgroup of colorectal carcinomas with microsatellite instability: a whole‐section immunohistochemical analysis

Abstract: The aim of this study is to establish heat shock protein 110 (HSP110) as a prognostic biomarker of colorectal carcinomas (CRCs) with microsatellite instability-high (MSI-H) by considering the intratumoral heterogeneity of HSP110 expression. We performed whole-section immunohistochemistry (IHC) for wild-type HSP110 (HSP110wt) in 164 MSI-H CRCs. The intensity of the HSP110wt expression in tumor cells was semiquantitatively scored (0/1/2/3), and the HSP110wt expression status of each tumor was classified as low o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
(38 reference statements)
3
11
0
Order By: Relevance
“…However, Kawai et al, 21 showed that a high HSP105 score was significantly associated with a favorable prognosis in patients with urinary bladder cancer treated with radical cystectomy. In line with our study, the poor prognosis was also associated with HSP 105 overexpression in myeloblastic syndromes, 8 in colorectal carcinomas 22 and in gastric cancer. 23 Different findings suggest that HSP105 may function differently in bladder cancer or elsewhere, compared to oral squamous cell carcinoma and squamous cell carcinoma of the lung.…”
Section: Accepted Articlesupporting
confidence: 91%
“…However, Kawai et al, 21 showed that a high HSP105 score was significantly associated with a favorable prognosis in patients with urinary bladder cancer treated with radical cystectomy. In line with our study, the poor prognosis was also associated with HSP 105 overexpression in myeloblastic syndromes, 8 in colorectal carcinomas 22 and in gastric cancer. 23 Different findings suggest that HSP105 may function differently in bladder cancer or elsewhere, compared to oral squamous cell carcinoma and squamous cell carcinoma of the lung.…”
Section: Accepted Articlesupporting
confidence: 91%
“…Another 42 records had insufficient data for HR calculation. Finally, 11 articles with 2269 patients were used [21][22][23][25][26][27][28][29][30][31][32]. The 11 articles had a sample size of 167 to 256 (average 206) (Table 1).…”
Section: Included Studies and Characteristicsmentioning
confidence: 99%
“…Studies have shown that Hsp70 expression is upregulated in various carcinoma tissues and could be a potential biomarker [7]. Besides, previous studies have reported that Hsp70 overexpression is associated with poor survival in some cancers, including breast carcinoma [8][9][10], esophageal adenocarcinoma [11], non-small-cell lung cancer [12], prostate cancer [13,14], gastric cancer [15,16], leukemia [17], hepatocellular carcinoma [18,19], pancreatic cancer [20], and colon cancer [21][22][23]. However, no study has reported the relationship between the Hsp70 expression level and prognosis of colorectal cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Hwang et al described increased HSP110 expression in cell lines from metastatic compared to non-metastatic CRC [62]. Kim et al found better disease free survival in patients with microsatellite-instable (MMR deficient) CRC characterized by HSP110 downregulation; explaining this by deletion of the HSP110 T17 gene, which is associated with genomic instability in MMR deficient tumors [67,68]. The same was described in gastric cancer [69].…”
Section: Discussionmentioning
confidence: 84%